Design and control a myoelectric prosthetic limb for trans humeral amputation - Dounia, Melloul (2021)
The loss of an upper limb can significantly affect the level of the potential and capability of performing everyday life and social activities. Most of the prevalent prosthetic devices contribute in a poor way in order to provide ideal performance to the amputees, due to many obstructions in the design, such as the range of motion, using many components which makes the prosthetic device heavy and complex. In addition, the high price makes it hard for many amputees to own a prosthetic device. Therefore, the objective of this research is to produce a prosthetic arm that is simple, lightweight, and affordable for amputees to assist them in daily life. The design is done using Solidworks software. The prosthetic device aims to provide one degree of freedom with a high range of motion up to 120◦ for the elbow. The material used for printing the device is the Polylactic acid (PLA) due to its strength and low cost. Electromyography signals generated from the biceps muscle has been used to control the arm movement. G15 cube servo motor has been chosen as the actuator for the elbow system. Experimental results show that the G15 servo motor can rotate from 180◦ to 340◦ when the electromyography sensor is located at the right position of the bicep muscle. In conclusion, a simple and low cos prosthetic arm is produced for the amputees and handicapped people to assist their performance in everyday life and social activities.